In attesa di un paradigma condiviso Commentari a Esodo - Galvagno, Germano 1968- (2017)
Review article
Keywords: Albertz, Rainer; Bible. Exodus -- Commentaries; Hamilton, Victor P; Utzschneider, Helmut; Rezension